Anterior cruciate ligament graft positioning, tensioning and twisting. - Amis,AA; Jakob,RP (Knee Surg Sports Traumatol Arthrosc, 1998)
This paper reports on a scientific workshop to study anterior cruciate ligament (ACL) reconstruction. The aim is to present recommendations for ACL reconstruction methods that will be of use for surgeons. A study of knee anatomy and graft placement concluded that the tibial attachment must be posterior enough to avoid graft impingement against the femur, and methods to attain this were presented. On the femur, poor graft placement leads to excessive changes of the graft attachment site separation distance as the knee flexes, and the worst case corresponds to the attachment being too far anterior. It was agreed that there were typical patterns of graft tension changes as the knee flexes, and that grafts should be tensioned close to full knee extension. A typical tensioning protocol would be 60 N tension applied at 10 degrees of flexion. It was recognised that graft remodelling caused uncontrollable tension changes post-operation. Graft twisting, to recreate the anatomical spiral of ACL fibres seen in the flexed knee, was also discussed.